2014
DOI: 10.1002/mnfr.201400126
|View full text |Cite
|
Sign up to set email alerts
|

Caco‐2 accumulation of lutein is greater from human milk than from infant formula despite similar bioaccessibility

Abstract: These data suggest that the bioavailability of carotenoids is greater from human milk than infant formula primarily due to intestinal absorptive processes, and that absorption of lutein is potentiated by factors from human milk especially at low lutein concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…A research carried out in infant rhesus macaques have also confirmed that feeding those animals with a mixture of feed enriched with carotenoids increases the saturation degree of their brain tissue in lutein but the increase in the amount of β-carotene, zeaxanthin and lycopene was negligible and below threshold of detection, what suggests the significance of lutein for the developing brain [ 123 ]. Due to lower bioaccessibility of lutein from infant formulas, it is necessary to consider a 4.5-fold increase in its concentration in relation to the levels found in breast milk [ 118 , 122 , 124 ].…”
Section: Infant Feeding Methods and Infant Carotenoid Statusmentioning
confidence: 99%
“…A research carried out in infant rhesus macaques have also confirmed that feeding those animals with a mixture of feed enriched with carotenoids increases the saturation degree of their brain tissue in lutein but the increase in the amount of β-carotene, zeaxanthin and lycopene was negligible and below threshold of detection, what suggests the significance of lutein for the developing brain [ 123 ]. Due to lower bioaccessibility of lutein from infant formulas, it is necessary to consider a 4.5-fold increase in its concentration in relation to the levels found in breast milk [ 118 , 122 , 124 ].…”
Section: Infant Feeding Methods and Infant Carotenoid Statusmentioning
confidence: 99%
“…Carotenoids were extracted from infant and maternal plasma in blinded, randomized order according to the method of Lipkie, et al [ 23 ]. Briefly, 100 μL plasma was deproteinized with 250 μL methanol, and extracted 3 times with 1 mL 1:2 acetone/petroleum ether with 0.1% BHT.…”
Section: Methodsmentioning
confidence: 99%
“…Breast-milk carotenoids are related to maternal serum carotenoids (107), which are influenced not only by diet but also likely by conditions known to influence serum carotenoid levels, such as obesity, smoking, and alcohol use and markers of inflammation (63). L in breast milk appears to be approximately fourfold more bioavailable than L in infant formulas to date (22, 106). Given the presence and accumulation of L and Z in the eye in gestation and infancy, and the potential for influence on lifelong vision, additional research is critically needed to establish requirements for L and Z intake in infancy.…”
Section: Accumulation Of Lutein and Isomers Over The Neonatal Periodmentioning
confidence: 99%